EFEK PENAMBAHAN PROPILEN GLIKOL ALGINAT DAN ISOLAT PROTEIN KEDELAI TERHADAP MUTU FISIK DAN MUTU PENERIMAAN MI JAGUNG - Fahim Muhammad Taqi; Subarna Subarna; Tjahja Muhandri; Rarasari Clorinita Utomo (Jurnal Teknologi dan Industri Pangan, 2018)
Corn noodle is a potential product to be developed in non-wheat producing countries; however the texture is generally less preferred than wheat noodles. The addition of propylene glycol alginate (PGA) and soy protein isolate (SPI) to the dough was expected to decrease the hardness of corn noodles and in-crease its protein content. This study aimed to evaluate the effect of PGA (0, 0.25, 0.5, 0.75, and 1%) and SPI (0, 5, and 10%) addition on corn noodle rheology. Five parameters were analyzed i.e. cooking loss, elongation, hardness, cohesiveness and stickiness. A hedonic rating test was also performed to evaluate the corn noodle organoleptic quality. The results showed that the addition of PGA decreased the cooking loss and hardness, but increased the elongation and cohessiveness. While the addition of SPI decreased the cooking loss and cohessiveness (at PGA level 0 and 0.25%), it increased hardness and elongation (at PGA level 0%). Based on the hedonic test, corn noodle with 0.5% PGA without the addition of SPI was the most preferred formula.